David Goodis’s Noir Fiction: The American Dream’s Paralysis - Robert Lance Snyder (European Journal of American Studies)
In its depiction of marginalized characters trapped within inner-city slums, David Goodis’s postwar fiction of the late 1940s through the 1950s constitutes a noir critique of the American Dream’s paralysis. The defining elements of that paradigm—romantic fulfillment, family cohesion, upward mobility, suburban escape, egalitarian success, material prosperity—are systematically shown to be beyond attainment by the underprivileged and, thus, a mechanism of social victimization. At the same time, despite his oeuvre’s unremitting bleakness, Goodis valorizes his protagonists’ capacity for endurance amid their alienation and disenfranchisement. During the fraught era of Cold War anxiety masked by mainstream conformism, this author’s down-and-outers recognize the truth that “There’s no success like failure, / And … failure’s no success at all.” His pulp novels significantly extend late-modernist themes of fragmentation, entropy, and despair.